MELT INCLUSION FORMATION MECHANISMS AND COMPOSITIONAL EFFECTS IN HIGH-AN FELDSPAR AND HIGH-FO OLIVINE IN ANHYDROUS MAFIC SILICATE LIQUIDS - Kohut E.; Nielsen R.L. (My University, 2004)
Important aspects of melt inclusion formation and potential compositions effects have been addressed through a series of experiments using anorthite/fosterite saturated anhydrous mafic liquids. Experimental charges were cooled from 1,300 to 1,230 and 1,210C at rates of 1–10/min followed by 0–24h isothermal periods. Hopper and skeletal crystal morphologies with variable degrees of completeness developed during the cooling period. Planar overgrowth of these textures during isothermal periods led to the formation of inclusions, the majority of which formed after 6h of isothermal run time. We suggest that the change in morphologies is related to a decrease in growth rates and changes in dominant growth mechanisms. In general, inclusion compositions were uniform and similar to the host glass, indicating that with the isothermal times required for most inclusions to form, a boundary layer was not entrapped that could be detected within the limits of our analyses.